Chronic stress-induced downregulation of MFN1 contributes to fatty liver in chickens - Zhang, Ke; Yu, Hui; Chen, Huimin; Guan, Ziting; Wang, Xiaoyu; Liu, Jie; Zhao, Mindie; Zhao, Ruqian; Yang, Dancheng; Wu, Lei (Frontiers in Veterinary Science, 2025)
BackgroundChronic stress is a major contributor to Fatty Liver Syndrome (FLS) in fast-growing broilers, leading to physiological dysfunctions that compromise growth and immune response. This study aimed to investigate the effects of chronic stress on hepatic lipid metabolism and mitochondrial dynamics in broilers.MethodForty 1-day-old male AA broilers were randomly allocated into two groups (n = 20): control (CON) and corticosterone-treated (CORT). From day 38, the CORT group received twice-daily subcutaneous injections of CORT (4 mg/kg/day) for 7 days to simulate in vivo chronic stress model. The loss-of-function approaches in cell culture models were also applied to investigate the role of MFN1 in CORT-induced mitochondrial dysfunction.ResultsChronic CORT treatment induced significant hepatic steatosis and liver injury in broilers. Furthermore, CORT disrupted mitochondrial function, as indicated by excessive mitochondrial fragmentation, a pronounced decrease in mitochondrial membrane potential (MMP), and aberrant oxidative stress responses in both in vivo and in vitro models. Studies showed that glucocorticoid receptor (GR)-mediated downregulation of mitofusin 1 (MFN1) plays a critical role in CORT-induced disruption of lipid metabolism. Importantly, restoration of MFN1 expression effectively rescued mitochondrial morphology and function and attenuated lipid accumulation in hepatocytes.ConclusionThis study reveals a key mechanism by which chronic stress impairs mitochondrial fusion via GR-mediated suppression of MFN1, driving fatty liver development in broilers. These findings underscore the critical role of MFN1 in mitochondrial dynamics and lipid metabolism, offering novel insights for potential therapeutic strategies against fatty liver disease in poultry.